Konsep Model Teori Ramona T. Mercer Pada Asuhan Keperawatan Ibu Melahirkan - Rika Astri Novianti; Irna Nursanti (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2024)
Ramona Thieme Mercer was born on October 4, 1929 is the author of the middle class theory of nursing known as the achievement of the maternal role. Mercer began her Nursing career in 1950, when she received a Diploma from St. Mary's. Margaret's School of Nursing in Montgomery Alabama. Mercer's theory is an example of a middle range theory, it has a lower abstraction that is derived from other theories so that it can be applied to more specific areas of nursing. A very interesting thing, of course, is when a nurse is able to translate how to develop this theory, it becomes easier to apply to patients. Maternal Role Attainment proposed by Mercer follows Bronfenbrenner's work in 1979 which is known as the bird's nest circle which includes a set of microsystem, mesosystem and macrosystem cycles. The application of the becoming a mother model in providing nursing care to postpartum clients is carried out to help clients achieve their role as a mother. So that the mother can provide good care for the baby and the baby can be fulfilled in psychosocial terms.